Inocybe aureocitrina (Inocybaceae), a new species of section Rimosae from Mediterranean evergreen oak forests - ESTEVE-RAVENTóS, F (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
The new agaricoid species Inocybe aureocitrina, belonging to section Rimosae, is described and illustrated based on morphological and ecological characters. It is recognized by the pale citrine yellow when young to golden yellow or orange yellow pileus colour at maturity, habitat in evergreen oak calcareous forests and especially by the rather small spores, broadly ellipsoid and not reniform in profile. A comparison with the holotypes of two close taxa with yellowish colours, e.g. Inocybe obsoleta var. lutea and Inocybe fastigiata var. cerina, is presented. Illustrations of the macro- and micro-morphological features of this new species are given.
doi: 10.1080/11263504.2013.877532
Keywords: Evergreen oak forests; Inocybe fastigiata var. cerina; Inocybe obsoleta var. lutea; Mediterranean ecosystems; morphology; Spanish mycobiota; taxonomy

Prediction of planted seedling survival of five Mediterranean species based on initial seedling morphology - Tsakaldimi, Marianthi; Ganatsas, Petros; JACOBS, DOUGLASS F (New Forests, 2012)
Field performance can be predicted by evaluating nursery stock quality, but optimal morphological variables for use in these assessments may vary by species especially under dry Mediterranean conditions. Our objective was to identify initial seedling morphological characteristics that successfully predict ﬁeld performance of ﬁve Mediterranean species (Pinus halepensis, Quercus ilex, Quercus coccifera, Ceratonia silqua and Pistacia lentiscus). Container seedling morphology was evaluated following the nursery phase, and then seedlings were outplanted in the ﬁeld where ﬁeld survival was monitored for two successive years. Results indicate that survival can successfully be predicted from seedling initial morphological characteristics for all these species, yet not all the initial characteristics were good predictors. Survival of P. halepensis and Pist. lentiscus seedlings was positively correlated to initial seedling root-collar diameter, total dry weight and Dickson’s quality index, and can be reliably predicted by these variables. In contrast, seedling ﬁeld survival of the two Mediterranean evergreen oak species was correlated with few initial morphological attributes; initial diameter provided an accurate index to predict second-year outplanting survival for both species while height/diameter was a good survival predictor for Q. coccifera seedlings. For C. siliqua seedlings, seedlings with larger initial diameter and total biomass survive better in the ﬁeld. Thus, diameter was the common variable that accurately predicted survival for all species, which should be [5 mm for P. halepensis seedlings and[7 mm for the remaining species.
Keywords: Field performance; morphology; outplanting; Prediction models; seedling quality

Relação entre as Características Morfológicas e a Qualidade da Cortiça - Pestana, Miguel; Carneiro, Luís; Lousada, José; Sardinha, Raúl (Silva Lusitana, 2011)
. The main drive of this study was to contribute for a better knowledge about the relationship between the quality of cork and its morphology, aiming to finding out the predictive capacity of the morphological characteristics and their weight to discriminate and select cork quality. Board cork samples were taken out from 9 sample trees (3 trees x 3 sites) and they were prepared to allow quantitative classification according to punctuation classification as described by CARVALHO (1992). Data analysis was done using numerical taxonomy methods. Results generated allow emphasizing that: • The use of punctuation criteria showed the usefulness and significance of some morphological characteristics to segregate cork quality; • Good quality corks were characterized by higher values of the belly's color and low values of the belly’s relief, and its unevenness, and the size and density of the inclusions in the cork mass as well; • Bad quality corks showed a set of dominant morphological characteristics: density, distribution, aggregation and size variation of lenticels and a pronounced relief and also the size of incrustations on the belly; • The introduction of one more parameters – apparent density (DA) – in the morphological analysis did not alter quality classification
Keywords: Cork; morphology; multivariate analyses; Quality

Chestnut and acorn starch properties affected by isolation methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Starch - Stärke, 2010)
Starches from chestnut (Castanea sativa Mill.) and acorns (Quercus suber Lam. and Q. rotundifolia Lam.) were isolated from dried fruits using four different methods. These involved a physicochemical and/or an enzymatic treatment followed by centrifugation and sieving: (i) low shear at alkaline pH – LSA, (ii) high shear in water – HSW, (iii) enzymatic treatment at low shear – LSE, (iv) LSA and using successively three sieves – LSA3S. Raw yield, purity, colour parameters, morphology, protein, fat, ash, reducing sugars and amylose contents, damaged starch content and viscoamylographic proﬁles were studied in isolated starches, presenting different properties through different methods. In general, chestnut starch seems to be poorly resistant to extraction methodologies as shown by the damaged starch content and viscoamylographic properties encountered during this study. Moreover, acorn starches exhibited cross-linked amylographic patterns. For all the tested raw materials, the LSA3S isolation method always higher yield and purity of starches. Gelatinization temperature and peak consistency were also higher than those shown by starches produced by the other methods, a less damaged structure was also evident. In conclusion, it seems that this method is the most suitable to produce starch for food ingredient usage.
Keywords: acorn; chestnut; morphology; physicochemical properties; starch isolation methods

Effect of drying temperatures on chemical and morphological properties of acorn flours - Correia, Paula R.; Leitão, António E.; Beirão-da-Costa, Maria L. (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.
Keywords: Acorn (Quercus suber and Quercus rotundifolia); chemical properties; drying; morphology

Effect of drying temperatures on chemical and morphological properties of acorn flours - Correia, Paula R.; Leitão, António E.; Beirão-da-Costa, Maria L. (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.
Keywords: Acorn (Quercus suber and Quercus rotundifolia); chemical properties; drying; morphology

Morphological-anatomical characterization and identification of Tomentella ectomycorrhizas. - Jakucs, Erzsébet; Eros-Honti, Zsolt (Mycorrhiza, 2008)
Over the last two decades, much information has been gathered on the ectomycorrhizal fungus community composition of plant associations of boreal, temperate, and tropical regions. Worldwide, Tomentella ectomycorrhizas (ECM) are often common and dominant in the mycorrhizosphere of coniferous and deciduous forests. They are present under different environmental conditions and associate with diverse plant hosts. Tomentella sporocarps, however, are rarely found aboveground, so Tomentella species are often missing from fungus community studies based on fruit-body presence. Tomentella is a resupinate genus of Thelephoraceae (Basidiomycota) forming black-brown, brown, yellow, or ochre ECM on the roots of gymnosperm and angiosperm trees, distinguished by typical morphological-anatomical characteristics (clamped hyphae, angular mantle, surface network, special rhizomorphs and cystidia). In this paper, we review the taxonomic position and morphological-anatomical characteristics of Tomentella ECM. A short summary of the microscopic features used for distinguishing tomentelloids during morphotyping and identification is presented in order to support molecular and ecological studies of ectomycorrhizal fungus communities.
Keywords: Anatomy; ECM; ectomycorrhiza; identification; morphology; Tomentella

Morphological and molecular characterisation of a new awl nematode, Dolichodorus mediterraneus sp. n. (Nematoda: Dolichodoridae), from Spain - Jiménez-Guirado, D; Murillo Navarro, R; Liébanas, Gracia; Landa, Blanca B; Castillo, Pablo (Nematology, 2007)
A new species of awl nematode, Dolichodorus mediterraneus sp. n., is described from southern Spain. The new species is described and illustrated by light microscopy and scanning electron microscopy studies from specimens collected in a sandy soil around roots of cork oak (Quercus suber L.) from Hato Raton, Aznalcázar (Seville), southern Spain. Dolichodorus mediterraneus sp. n. is characterised by a prominent, rounded, lip region, which is offset from the body and has four to six very fine annuli; lateral fields areolated with three lines, ending posterior to anus level; tail 72-122 μm long, abruptly tapering to an acuminate, often spicate, terminus; tail projection 51-79 μ m long; spicules ventrally arcuate, 33-42 μm long; gubernaculum slightly ventrally curved, 14-22 μm long. Scanning electron microscopy observations showed a similar en face pattern to other Dolichodorus spp. Molecular data from the ribosomal large subunit D2-D3 expansion segment of 28S rDNA from paratypes yielded a single fragment of approximately 800 bp. This is the first record of the genus Dolichodorus in Spain and only the second in Europe. A key to species is provided.
Keywords: Description; key; morphology; Morphometrics; Ribosomal Large Subunit D2-D3 Region; SEM; taxonomy

Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests - Bordera, Santiago; Hernández-Rodríguez, Estefanía (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.
Keywords: Gnotus; habitat; morphology; new species; phenology (PG); Stibeutes

Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests - Bordera, Santiago; Hernández-Rodríguez, Estefanía (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.
Keywords: Gnotus; habitat; morphology; new species; phenology (PG); Stibeutes

IDENTIFICACIÓN Y DESCRIPCIÓN DE LAS ECTOMICORRIZAS ZONA QUEMADA Y UNA ZONA SIN ALTERAR DEL CARRASCAL DE NAZAR ( NAVARRA ) - Román, D E; Miguel, M D E (Publicaciones de Biología, Universidad de Navarra, Serie Botánica, 2000)
Since 1998, a field study has been undertaken in a Quercus ilex L. subsp. ballota (Desf.) Samp. forest located in Nazar (Navarra, Spain). This study aims to establish a qualitative and quantitative comparison between the ectomycorrhizal morphotypes which have been collected, described and identified in a burned site and in a non- disturbed one within this forest. Thus, this study aims to contribute to the knowledge of the ectomycorrhizae associated with evergreen oak in field conditions, because most of the studies on evergreen oak ectomycorrhizae are related to truffle growing or artificial mycorrhization in the nursery.
Keywords: Ectomycorrhizae; fire; identification; morphology; Quercus ilex; Tuber melanosporum

IDENTIFICACIÓN Y DESCRIPCIÓN DE LAS ECTOMICORRIZAS ZONA QUEMADA Y UNA ZONA SIN ALTERAR DEL CARRASCAL DE NAZAR ( NAVARRA ) - Román, D. E.; Miguel, M. D. E. (Publicaciones de Biología, Universidad de Navarra, Serie Botánica, 2000)
Since 1998, a field study has been undertaken in a Quercus ilex L. subsp. ballota (Desf.) Samp. forest located in Nazar (Navarra, Spain). This study aims to establish a qualitative and quantitative comparison between the ectomycorrhizal morphotypes which have been collected, described and identified in a burned site and in a non- disturbed one within this forest. Thus, this study aims to contribute to the knowledge of the ectomycorrhizae associated with evergreen oak in field conditions, because most of the studies on evergreen oak ectomycorrhizae are related to truffle growing or artificial mycorrhization in the nursery.
Keywords: Ectomycorrhizae; fire; identification; morphology; Quercus ilex; Tuber melanosporum

Intraspecific variation of growth and adaptive traits in European oak species - Kleinschmit, J (Ann. For. Sci., 1993)
According to various reports, 200-450 oak species including hybrid populations exist worldwide, with 24 of these - including 3 hybrid forms - having their natural range within Europe. They all belong to the subgenus Lepidobalanus. The most important section is robur with 21 species. The European species belong to both deciduous (15 species) and evergreen (9 species) oaks. Some difficulties in clear morphological and physiological definition of the species involved is caused by hybridization. Most studies into intraspecific variation exist for the species Quercus robur L and Quercus petraea (Matt) Liebl. Some information is available for Quercus cerris L, Quercus virginiana Ten (= Q dalechampii Wenz), Quercus ilex L and Quercus suber L, based on comparative plantations. In addition, a considerable number of morphological, physiological and biochemical studies based on natural populations exist which are not completely covered in this review paper. For most characters observed, oaks exhibit a wide variation. This is not only the case for morphological traits of pollen, seed, wood and plants but also for physiological traits and phenology which have great adaptive importance. Provenance experiments and progeny tests started as early as 1877. Most of these were only of local importance. This is partly due to the fact that acorns can only be stored for a limited period and flowering is irregular. However, the results available show that the choice of provenance can be important for the successful economic management of plantations. Variability of leaves, phenology, form, growth, wood and bark, roots, seed and flowering has been discussed separately. Improvement via selection and testing seems to be promising due to the considerable between-population and within-provenance variation. Vegetative propagation has been developed for some species by grafting, cutting propagation and in vitro propagation. Tree breeding approaches have also been discussed.
Keywords: intraspecific variation; morphology; progeny test; provenance; Quercus; vegetative propagation